Розробка новітніх ресурсоефективних підходів до вирішення проблеми очистки нафтовмісних стічних вод - Khokhotva, Oleksandr P.; Ivanenko , Olena I.; Tereshchenko, Oksana M. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2023)
The article noted that the pollution of surface water bodies by oil products as part of wastewater in Ukraine in 2020 reached 246.6 tons. For aquatic organisms, oil and oil products are highly toxic substances and belong to the group of nerve poisons. Most of the wastewater generated today in industry is subject to purification from petroleum products before discharge into the environment, however, existing purification technologies do not fully meet modern requirements. Electrochemical cleaning methods have a number of significant advantages over reagent methods: the salt content in water does not increase, which plays an important role in the organization of circulating water supply systems; less sediment is formed; the technological scheme of cleaning is simplified; there is no need to organize a reagent farm; small production areas are required for the placement of electrochemical treatment plants. The operation of electric cleaning plants is simple due to their high manufacturability and the possibility of automation. As a result of research, the optimal conditions for electroflotation water purification from oil products have been determined. The dependence of the degree of purification on the material of the anode, the pH of the initial solution and the current density was studied. It was established that the best effect is achieved in the pH range of 5-7 at current densities of 0.25-0.3 A/dm2. In the presence of sulfates, cleaning proceeds better than in the presence of chlorides, since Cl– ions intensify the point breakdown of the anode material. Among the studied materials, 08кп steel can be recommended as an anode. The nature of the electrochemical dissolution of 08kp steel depending on its preliminary treatment and the effect of such treatment on the degree of purification of water from petroleum products was studied. It is shown that when adding sulfanol НП-3 with flocculant ВПК-402 to oil-containing water, a water-insoluble complex is formed, which contributes to a more complete purification of water from oil and oil products.